Simplify. Show your work. (3x−5)(2x+7)

Question

Simplify. Show your work.

(3x−5)(2x+7)

in progress 0
Nevaeh 3 months 2022-02-19T06:35:12+00:00 2 Answers 0 views 0

Answers ( )

    0
    2022-02-19T06:36:19+00:00

    Answer:

    =6x^2+11x−35

    Step-by-step explanation:

    (3x+−5)(2x+7)

    =(3x)(2x)+(3x)(7)+(−5)(2x)+(−5)(7)

    =6×2+21x−10x−35

    =6×2+11x−35

    0
    2022-02-19T06:36:21+00:00

    Answer:

    6x^2 + 11x -35

    Step-by-step explanation:

    Distribute so,

    (3x)(2x)=6x^2

    then,

    (3x)(7)=21x

    (-5)(2x)=-10x

    21x – 10x = 11x

    then,

    (-5)(7)=-35

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )